Clinical outcomes of patients undergoing percutaneous left atrial appendage occlusion in general anaesthesia or conscious sedation: data from the prospective global Amplatzer Amulet Occluder Observational Study. Issue 3 (24th March 2021) - Piayda, Kerstin; Hellhammer, Katharina; Nielsen-Kudsk, Jens Erik; Schmidt, Boris; Mazzone, Patrizio; Berti, Sergio; Fischer, Sven; Lund, Juha; Montorfano, Matteo; Della Bella, Paolo; Gage, Ryan; Zeus, Tobias
Abstract : Objective: To evaluate the safety and efficacy of percutaneous left atrial appendage occlusion (LAAO) using conscious sedation (CS). Background: Several percutaneous structural heart disease interventions are safely and efficiently performed using CS instead of general anaesthesia (GA). This concept has not been evaluated in a large multicenter cohort of patients undergoing LAAO. Methods: Patients from the prospective, global Amplatzer Amulet Occluder Observational Study were divided into two groups (GA vs CS). Baseline information, periprocedural and postprocedural efficacy and complications, as well as outcomes through 7 days post implant were compared. Results: Patients undergoing transesophageal-guided implants were categorised by GA (n=607, 64%) or CS (n=342, 36%) usage. Mean age was 75 years in both groups. LAAO technical success was achieved in 99% of both groups. The procedure duration (GA: 35±22 min vs CS: 27±19 min, p<0.001), total amount of contrast medium (GA: 105±81 mL vs CS: 86±66 mL, p<0.001) and fluoroscopic time (GA: 13±9 min vs CS: 12±13 min, p<0.001) were less in CS cases. Procedure-related or device-related serious adverse events during the first 7 days were numerically higher in the CS group (GA: 4.9% vs CS: 7.6%, p=0.114). Peridevice residual flow was absent or ≤5 mm 1–3 months after the procedure in 99.7% of the GA and in 100% of the CS group (p=1.000). Conclusions: In a large global study, LAAO with the Amplatzer Amulet occluder is safe and feasible using CS. Procedure duration and total amount of contrast were less with CS than GA cases. Trial registration number: NCT02447081; Results .